The Impact of Helicobacter pylori on Lesion Type and Matrix Metalloproteinase-9 Expression in Laryngeal Tumors - Wasan Abdul-elah Bakir; Refif Sabih Al-Shawk; Mais Ibrahim Alsikafi; Shaimaa Rahem Al-Salihy (Diyala Journal of Medicine, 2025)
Background: Helicobacter pylori and matrix metalloproteinase-9 (MMP-9) play a significant part in the pathophysiological processes and expression of carcinogenesis, particularly in laryngeal Squamous Cell Carcinoma (LSCC). Objective: Explore the link between the H. pylori bacterium, MMP-9 expression, and laryngeal squamous cell carcinoma development by examining the role of chronic inflammation and extracellular matrix remodeling in laryngeal carcinogenesis. Patients and Methods: This cross-sectional study recruited 118 tissue samples, including 58 malignant LSCC and 60 benign laryngeal polyps (BLP). Histopathological and immunohistochemical methods were used to assess the interplay of H. pylori, MMP-9, and smoking status in laryngeal tumors. Results: The prevalence of H. pylori was significantly higher in malignant lesions (63.79%) as compared to benign lesions (51.66%) (p=0.1). A significant correlation was found in patients with benign lesions between the level of MMP-9 and smoking and H. pylori status (r = 0.46, p = 0.001), and (r = 0.5, p = 0.001), respectively. While in patients with malignant lesions, the correlation test revealed a significant negative correlation between the level of MMP-9 and smoking status (r = -0.41, p 0.001), while H. pylori is a highest positively correlated with MMP-9 expression (r = 0.5, p = 0.001). The logistic regression analysis revealed that H. pylori infection could significantly predict high MMP-9 expression (OR =3.08, 95% CI: 1.15-8.28, p = 0.02). Conclusion: These findings highlight the crucial role of H. pylori infection and smoking in tumor progression through MMP-9-mediated extracellular matrix remodeling, inflammation, and immune modulation. Suggesting the potential impact of targeting H. pylori infection and MMP-9 activity for managing carcinogenesis. Keywords: Helicobacter pylori, MMP-9, laryngeal squamous cell carcinoma, Benign laryngeal polyps.